2013
DOI: 10.1108/mrjiam-01-2012-0468
|View full text |Cite
|
Sign up to set email alerts
|

Quality management and employees' attitudes: an example from certified enterprises

Abstract: Quality Management and Employees' Attitudes: An Example from Certified EnterprisesThis study investigates the implications of practices of the quality management system (QMS) in employees' attitudes in relation to job involvement, job satisfaction, career satisfaction and organizational commitment. This study was accomplished through the use of a survey by questionnaire. Twenty hypotheses related to QMS practices and the employees´ attitudes were formulated and tested.The results indicate that responsibility a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
21
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 20 publications
6
21
3
Order By: Relevance
“…The current study is consistent with previous research, which found that teamwork was significantly positive related to employees' job involvement (Ooi et al, 2007a). The result is consistent with the finding of a study by Batista et al (2013) which found that teamwork had a significant and positive correlation with job involvement.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The current study is consistent with previous research, which found that teamwork was significantly positive related to employees' job involvement (Ooi et al, 2007a). The result is consistent with the finding of a study by Batista et al (2013) which found that teamwork had a significant and positive correlation with job involvement.…”
Section: Discussionsupporting
confidence: 83%
“…However, the result is contrast with the finding of a study by Karia and Asaari (2006), which found that customer focus did not contribute to employees' job involvement. The result is inconsistent with previous research which found that customer focus did not demonstrate any favorable contribution to the employees' job involvement (Batista et al, 2013).…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Organizational commitment is the affective commitment that represents an employee's strong desire to remain a member of a particular organization when the opportunity to change jobs exists (Agarwal and Ramaswami, 1993). Affective commitment refers to the identification with involvement in, and emotional attachment to the organization (Allen and Meyer, 1996).TQM practices influence on employees' organizational commitment (Ooi et al, 2005;KariaandAsaari, 2006;Batista, et al, 2013). Training focused on broadening employees' knowledge and skills can represent opportunities for individual growth (Hunt (1992).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Training and education plays a critical role in maintaining high quality level which can be achieved through the best use of talent and activities available within the organization (TalibandRahman, 2010). Training and education was significantly positive related to employees' organizational commitment (Ooi et al, 2005;Karia and Asaari, 2006) but training and education did not show any favorable contribution to the organizational commitment (Batista, et al, 2013). Teamwork means working together and typically involves groups of interdependent employees who work cooperatively to achieve a common goal (Parker and Wall, 1998).Teamworkis a work arrangement that arguably has the capacity to enable cooperation and effective individual involvement and it represents a way of working (Gallear and Ghobadian, 2004).…”
Section: Literature Reviewmentioning
confidence: 99%